Halal Product Certification Assistance for Micro, Small and Medium Enterprises Aqila Food and Cake - Lina Susilowati; Nanik Sri Setyani; Munawaroh (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
The development of the halal industry is significant in countries where the majority of the population is Muslim. Jombang Regency has a Muslim population of 1,334,603 or around 98.5%. The halal label is important in marketing studies because consumers pay attention to the halal label printed on the product packaging. UMKM Akila Food and Cake is a business engaged in the food sector. The lack of knowledge about how to manage halal certification is one of the problems which then makes servants moved to provide assistance. The initial activity was in the form of socializing the importance of halal certification. Assistance by the service team and Mrs. Siti Indah Irawati as Halal Product Process Assistant from LSH ISNU Jombang is carried out by creating an Akila Food and Cake MSME account, entering data on the application for halal certification and completing the data. Halal product process assistants verify and validate business actors' statements. BPJH conducts system verification and validation of the results of assistance in the halal product process and issues Document Receipt Letters. Komtie Fatwa conducts fatwa hearings to determine product halalness and issue halal certification.